Characterization of an acetyl xylan esterase from the marine bacterium Ochrovirga pacifica and its synergism with xylanase on beechwood xylan - Hettiarachchi, Sachithra Amarin (Microb Cell Fact, 2019)
BACKGROUND: Acetyl xylan esterase plays an important role in the complete enzymatic hydrolysis of lignocellulosic materials. It hydrolyzes the ester linkages of acetic acid in xylan and supports and enhances the activity of xylanase. This study was conducted to identify and overexpress the acetyl xylan esterase (AXE) gene revealed by the genomic sequencing of the marine bacterium Ochrovirga pacifica. RESULTS: The AXE gene has an 864-bp open reading frame that encodes 287 aa and consists of an AXE domain from aa 60 to 274. Gene was cloned to pET-16b vector and expressed the recombinant AXE (rAXE) in Escherichia coli BL21 (DE3). The predicted molecular mass was 31.75 kDa. The maximum specific activity (40.08 U/mg) was recorded at the optimal temperature and pH which were 50 °C and pH 8.0, respectively. The thermal stability assay showed that AXE maintains its residual activity almost constantly throughout and after incubation at 45 °C for 120 min. The synergism of AXE with xylanase on beechwood xylan, increased the relative activity 1.41-fold. CONCLUSION: Resulted higher relative activity of rAXE with commercially available xylanase on beechwood xylan showed its potential for the use of rAXE in industrial purposes as a de-esterification enzyme to hydrolyze xylan and hemicellulose-like complex substrates. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12934-019-1169-y) contains supplementary material, which is available to authorized users.